Evaluation of Microbial Biofilm on The Surface of Two Different Types of Relining Materials in Vivo - Mohamed Hossam El-din Helmy (2013)
Arabic Summary.
Reference (84-102).
MD in Removable Prosthodontics
Cario University , Faculty of Oral & Dental Medicine .
Keywords: Removable prosthodontics